Perbandingan Efisiensi BPR Konvensional Dan BPR Syariah Provinsi Jawa Timur Dengan Pendekatan Non-Parametrik - Bahrina Almas (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2018)
This study aims to find out and explain the efficiency level comparison between Conventional Rural Banks and Sharia Rural Banks using Data Envelopment Analysis (DEA) method. This research is a type of quantitative research using secondary. The sample used in this study amounted to 10 BPR, consisting of 5 samples of Conventional Rural Banks and 5 samples of Islamic Rural Banks during the period March 2013 to December 2017. Input variables in this study were total assets, third party funds and labor costs, while variables the output used is credit or financing and operating income. The results of the analysis using the Data Envelopment Analysis (DEA) method show that there are two BPR from 5 samples of efficient Conventional Rural Banks, while there are no efficient BPR from 5 Sharia Rural Banks samples.